A chiral selectivity relaxed paralog of DTD for proofreading tRNA mischarging in Animalia - Santosh Kumar Kuncha (Nature Portfolio, 2018)
The number of tRNA isodecoders has expanded significantly during evolution, which has resulted in ambiguity in tRNA selection by synthetases. Here the authors identify and characterize a dedicated proofreading factor that eliminates errors caused by ambiguity in tRNA selection by eukaryotic tRNA synthetases.